2014
DOI: 10.1007/s12192-013-0480-5
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate (S1P) promotes mitochondrial biogenesis in Hep G2 cells by activating Peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α)

Abstract: Sphingosine 1-phosphate (S1P), a potent bioactive phospholipid, has been reported to regulate a broad spectrum of biological processes. However, little is known regarding S1P's effects on mitochondrial function. In this study, we investigated the S1P's effects on the Peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) signaling pathway and mitochondrial biogenesis in Hep G2 cells. Our results indicate that administration of S1P leads to a significant upregulation of mitochondrial DNA replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Interestingly, a recent study using HepG2 cells (a human hepatocellular carcinoma line) has shown that S1P increases mitochondrial biogenesis and stimulates the expression of PGC1a (68). This study also showed the effects of S1P on mitochondrial biogenesis (e.g., up-regulation of mitochondrial DNA replication) to be S1P 2 dependent (68). Although limited literature is available on a vascular role for PGC1b, PGC1b overexpression in vascular smooth muscle cells inhibits proliferation and neointima hyperplasia, with a reduction in PGC1b detected in the arteries following balloon injury (69).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study using HepG2 cells (a human hepatocellular carcinoma line) has shown that S1P increases mitochondrial biogenesis and stimulates the expression of PGC1a (68). This study also showed the effects of S1P on mitochondrial biogenesis (e.g., up-regulation of mitochondrial DNA replication) to be S1P 2 dependent (68). Although limited literature is available on a vascular role for PGC1b, PGC1b overexpression in vascular smooth muscle cells inhibits proliferation and neointima hyperplasia, with a reduction in PGC1b detected in the arteries following balloon injury (69).…”
Section: Discussionmentioning
confidence: 99%
“…respiratory dysfunction and subsequent energy metabolism disorders, which can be restored by exogenous S1P treatment (Strub et al, 2011). Furthermore, S1P has been proved to promote mitochondrial biogenesis by increasing mitochondrial DNA replication, transcription and mitochondrial mass (Shen et al, 2014). There is also evidence showing that S1P treatment can alleviate oxygen-glucose deprivation (OGD) induced inner membrane depolarization, which can induce the formation of MMP (mitochondrial membrane permeability) and directly affect mitochondrial function (Agudo-López et al, 2010).…”
Section: S1p As a Neuroprotective Factormentioning
confidence: 99%
“…Increased production of reactive oxygen species (ROS) and neurotoxins under pathological circumstances has a negative effect in mitochondrial abundance and the copy number of mitochondrial DNA (mtDNA) . Mitochondrial biogenesis plays a critical role in maintaining normal energy metabolism, mitochondrial homeostasis, and quality control . Mitochondrial biogenesis is mainly regulated by the peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α) and its downstream molecules nuclear respiratory factor 1 (NRF‐1) and the mitochondrial transcription factor A (TFAM).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Mitochondrial biogenesis plays a critical role in maintaining normal energy metabolism, mitochondrial homeostasis, and quality control. 5 Mitochondrial biogenesis is mainly regulated by the peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) and its downstream molecules nuclear respiratory factor 1 (NRF-1) and the mitochondrial transcription factor A (TFAM). NRF-1 is a nuclear transcriptional factor that is responsible for the transcription of nuclear genes that code subunits of the oxidative phosphorylation system.…”
Section: Introductionmentioning
confidence: 99%